Effect of implementation of the WHO intrapartum care model on maternal and neonatal outcomes: a randomized control trial - Somayeh Abdolalipour; Shamsi Abbasalizadeh; Sakineh Mohammad-Al; Fatemeh Abbasalizadeh; Shayesteh Jahanfar; Fatemeh Raphi; Mojgan Mirghafourvand (BMC, 2024)
Abstract Background In 2018, the World Health Organization published a set of recommendations for further emphasis on the quality of intrapartum care to improve the childbirth experience. This study aimed to determine the effects of the WHO intrapartum care model on the childbirth experience, fear of childbirth, the quality of intrapartum care (primary outcomes), as well as post-traumatic stress disorder symptoms, postpartum depression, the duration of childbirth stages, the frequency of vaginal childbirth, Apgar score less than 7, desire for subsequent childbearing, and exclusive breastfeeding in the 4 to 6 weeks postpartum period (secondary outcomes). Methods This study was a randomized controlled trial involving 108 pregnant women admitted to the maternity units of Al-Zahra and Taleghani hospitals in Tabriz-Iran. Participants were allocated to either the intervention group, which received care according to the ' 'intrapartum care model, or the control group, which received the' 'hospital's routine care, using the blocked randomization method. A Partograph chart was drawn for each participant during pregnancy. A delivery fear scale was completed by all participants both before the beginning of the active phase (pre-intervention) and during 7 to 8 cm dilation (post-intervention). Participants in both groups were followed up for 4 to 6 weeks after childbirth and were asked to complete questionnaires on childbirth experience, postpartum depression, and post-traumatic stress disorder symptoms, as well as the pregnancy and childbirth questionnaire and checklists on the desire to have children again and exclusive breastfeeding. The data were analyzed using independent T and Mann-Whitney U tests and analysis of covariance ANCOVA with adjustments for the parity variable and the baseline scores or childbirth fear. Results The average score for the childbirth experience total was notably higher in the intervention group (Adjusted Mean Difference (AMD) (95% Confidence Interval (CI)): 7.0 (0.6 to 0.8), p < 0.001). Similarly, the intrapartum care quality score exhibited a significant increase in the intervention group (AMD (95% CI): 7.0 (4.0 to 10), p < 0.001). Furthermore, the post-intervention fear of childbirth score demonstrated a substantial decrease in the intervention group (AMD (95% CI): -16.0 (-22.0 to -10.0), p < 0.001). No statistically significant differences were observed between the two groups in terms of mean scores for depression, PTSD symptoms, duration of childbirth stages, frequency of vaginal childbirth, Apgar score less than 7, and exclusive breastfeeding in the 4 to 6 weeks postpartum (p > 0.05). Conclusion The intrapartum care model endorsed by the World Health Organization (WHO) has demonstrated effectiveness in enhancing childbirth experiences and increasing maternal satisfaction with the quality of obstetric care. Additionally, it contributes to the reduction of fear associated with labor and childbirth. Future research endeavors should explore strategies to prioritize and integrate respectful, high-quality care during labor and childbirth alongside clinical measures.